Assessment of Hand Hygiene Knowledge and Practices among Private Dental Clinics in Munshiganj, Bangladesh: A Cross-Sectional Study (Update Dental College Journal, 2023)
Introduction: The study was performed to assess knowledge about infection control through hand-washing practices among dentists and paramedical professionals working at private dental clinics and provide help to identify and overcome obstruction towards proper hand hygiene pattern.Method: A questionnaire-based study was supervised at 15 different private dental clinics situated in the Munshiganj district of Bangladesh. Data on handwashing practices and other factors were collected from 60 samples during the months of November and December 2020. Site inspections of and washing facilities were also supervised. The data was analyzed on SPSS.Result: Majority (78.3%, 50.0% & 35.0%) of the respondents strongly agreed that hand washing helps to prevent spread of infection to the patients. Less than half (48.3%) of the respondents washed their hands before wearing gloves. 31 doctors claimed that hand washing is done after termination of duty while 10 claims that they wash hands after each examination (p< 0.001). And most of the doctors use antibacterial soap (p=0.004).Conclusion: The study wraps up that most of the health care providers had the education about the advantage of handwashing, but proper technique was not followed. The reasons given for not adopting handwashing practices were shortage of time, being busy with a greater number of patients, a skin reaction, and an unsuitable atmosphere.Update Dent. Coll. j: 2023; 13(1): 23-26